Benchmarking Supply Chain Flexibility using Data Envelopment Analysis. Issue 3 (1st January 2012) - More, Dileep; Subash Babu, A.
Organisations have been facing several disturbing events, problems and changes affecting overall performance of their Supply Chains (SCs). To be competitive by quickly responding to disruptions, building enough flexibility in SCs is emerging as a new business strategy. However, it is very difficult to identify how much flexibility is required in different functions of the SC, as it depends on the nature and level of uncertainty faced by the process, facility or organization. In this paper, SCF is logically attributed to a business function synonymously with the efficiency of the corresponding business unit, wherein the leveraging factors are treated as the inputs and the benefits as the outputs. Here, the Data Envelopment Analysis (DEA) approach is used as a benchmarking tool for deriving the advantage of optimisation in many ways.